(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Software metrics are developed and used by the many software organizations for the evaluation and confirmation of good code, working and maintenance of the software product. Software metrics measure and identify various types of software complexities such as size metrics, control flow metrics and data flow metrics. One of the significant objective of software metrics is that it is applicable to both a process and product metrics. Ndepend is the most advanced as well as flexible tool available in the market. We have ensured the Quality of the project by using Ndepend metrics. So we have concluded that software metrics are easy to understand and applicable on the software, so favourable among software professionals.It is most prevalent and important testing metrics used in organizations. Metrics are used to improve software productivity and quality. This thesis introduces the most commonly used software metrics proposed and reviews their use in constructing models of the software development process.